Self-Administered Screening for Mild Cognitive Impairment: Initial Validation of a Computerized Test Battery - Tornatore, Jane B; Hill, Emory; Laboff, Jo Anne; McGann, Mary E (The journal of neuropsychiatry and clinical neurosciences, 2005)
The Computer-Administered Neuropsychological Screen for Mild Cognitive Impairment (CANS-MCI), a computer administered, scored, and interpreted touch screen battery was evaluated for its ability to detect mild cognitive impairment. Subjects were three hundred ten community-dwelling elders who enrolled in an National Institute on Aging (NIA)-funded study. One-month test-retest reliability correlations were all significant (p<0.05-p<0.001). Concurrent validity correlations were all significant (p<0.001). A high level of diagnostic validity was attained relative to the Weschler Memory Scale-Revised (WMS-R) LMS-II test (p<0.001). Confirmatory factor analysis supported a three-factor model indicating the tests measure the intended cognitive dimensions of memory, language spatial fluency, and executive function mental control. Goodness-of-fit indicators were strong (Bentler Comparative Fit Index = 0.99; Root Mean Square Error of Approximation=0.055). Initial validation analyses indicate that the CANS-MCI shows promise of being a reliable, valid screening tool in determining whether more intensive testing for early cognitive impairment is warranted.